Animal Assisted Therapy Ikan Cupang Sebagai Teknik Distraksi Menurunkan Nyeri Pada Anak Prasekolah Yang Menjalani Prosedur Invasif - Atik Aryani; Rantiningsih Sumarni; Etty Eriyanti (Tribhuwana Tunggadewi University, 2026)
The experience of being hospitalized is often unpleasant for children. Preschoolers tend to respond to medical care with resistance and are less cooperative when they are in pain. If pain is not managed, it can lead to reduced cooperation and hinder the healing process. One nursing intervention to reduce pain involves using the distraction technique of Animal-Assisted Therapy (AAT) with betta fish. This study aims to analyze the effectiveness of AAT using betta fish as a distraction technique to reduce pain in children undergoing invasive procedures. This study employed a quasi-experimental design using a posttest-only with control group approach. The sampling technique used purposive sampling with 60 participants aged 3–5 years, divided into 30 in the intervention group and 30 in the control group. Research data were collected using the FLACC Scale (Face, Legs, Activity, Cry, Consolability) as a measure of pain in children, and the intervention involved the use of betta fish.The median pain score in the intervention group was 3, while the median pain score in the control group was 5. Based on the results of the Mann-Whitney test, a p-value of 0.001 (0.05) was obtained, indicating that betta fish-assisted therapy is effective as a distraction technique in reducing pain in preschool children undergoing invasive procedures. Recommendations for future research include measuring pain intensity and evaluating the effects of betta fish-assisted therapy on anxiety levels, fear, physiological responses, and children’s cooperation during invasive procedures, as well as the satisfaction of parents and healthcare providers.